Identification of superior commodities in the food crop subsector in Merauke Regency - Redu, Silas Tanggu; Pane, Lindon R (AGRICOLA, 2025)
The study investigated comparative and competitive food crop commodities in each district of Merauke Regency, South Papua Province, Indonesia, to support strategic agricultural development in the region. The research conducted from June to September 2024 uses a quantitative descriptive approach. Primary data comes from primary informants, such as the Head of the Food Crops, Horticulture, and Plantation Service, and secondary data from statistical reports and scientific literature. Using a Location Quotient (LQ) analysis, the study identified root crops (cassava, sweet potato, taro, and gembili) as the most dominant commodity found in almost all districts, while legumes (peanuts, mung beans, and soybeans) were concentrated in eight districts. Rice production is prominent in four districts (Kurik, Malind, Semangga, and Tanah Miring), while maize cultivation covers nine districts, including Kimaam, Okaba, Animha, and others. These findings underscore the potential for commodity-based agriculture development in Merauke Regency, highlighting the need for targeted interventions to optimize production, strengthen market access, develop farmer institutions, and improve supporting infrastructure. This research provides important insights for policymakers and stakeholders to advance the agricultural sector in the region, especially in the development of food crops.